2002
DOI: 10.1097/00042737-200207000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis and idiopathic retroperitoneal fibrosis: a rare association

Abstract: Primary biliary cirrhosis has rarely been reported to be associated with idiopathic retroperitoneal fibrosis. We describe the case of a 57-year-old man who was confirmed to have both conditions, reflecting the likely autoimmune aetiopathogenesis common to both disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…However, clinical features of an overlap of IgG4-RD and PBC remain unknown because of its rarity. All five PBC patients with AIP or idiopathic retroperitoneal fibrosis previously reported were male (6,7,(16)(17)(18). The proportions of women are 87% and 17-38% in PBC and IgG4-RD, respectively (1,19), thus suggesting that gender may be associated with the occurrence of IgG4-RD in PBC.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, clinical features of an overlap of IgG4-RD and PBC remain unknown because of its rarity. All five PBC patients with AIP or idiopathic retroperitoneal fibrosis previously reported were male (6,7,(16)(17)(18). The proportions of women are 87% and 17-38% in PBC and IgG4-RD, respectively (1,19), thus suggesting that gender may be associated with the occurrence of IgG4-RD in PBC.…”
Section: Discussionmentioning
confidence: 86%
“…Considering that two cases of an overlap of IgG4-SC and PBC with concurrent AIP have been reported (6,7), some PBC patients may have AIP. In addition, some PBC patients have been reported to have idiopathic retroperitoneal fibrosis (16)(17)(18), which is one of the manifestations of IgG4-RD (2). Therefore, a small subset of PBC patients may have IgG4-RD.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a few cases of overlapping PBC and idiopathic RPF have been reported. [ 24 , 25 ] It is suggested that a small subset of PBC patients may have IgG4-related RPF. However, the clinical features of overlapping IgG4-RD and PBC are unknown due to its rarity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a significant number of CECs have been detected in different diseases, such as acute coronary syndrome, sickle cell anemia, rickettsia and cytomegalovirus infection, SLE, ANCA-associated small-vessel vasculitis, Kawasaki disease, and SSc [14,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. In addition, in a large group of patients with SLE, we found a number of CECs higher than in normal controls [28], but lower with respect to that observed in patients with CP in the present study (mean values in SLE patients 44.5/mL, 95% CI 38.…”
Section: Discussionmentioning
confidence: 99%